2023
DOI: 10.1007/s10113-022-02018-7
|View full text |Cite
|
Sign up to set email alerts
|

Confronting climate change and livelihood: smallholder farmers’ perceptions and adaptation strategies in northeastern Burundi

Abstract: Rain-fed agriculture is the main source of livelihood for most of Burundi’s population, especially in the northeastern part of the country. This research is aimed at examining how smallholder farmers in the Northeastern region of Burundi perceive climate change and variability and at identifying the methods that are used to adapt, based on data from 200 small farmers and on actual weather data recorded between 1986 and 2017. We find that the majority of farmers (54%) perceive significant increases in temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…The difference between the average number of years of farming experience of men (21) and women ( 16) was statistically significant (p < 0.001). Experience maybe associated with a better understanding of climate change impacts and potential adaptation strategies (Batungwanayo et al, 2023), thereby explaining possible gender differences in choice or use of climate change adaptation strategies. The results also showed that almost all farmers (98%) in the study area relied on crop production as their main income source.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference between the average number of years of farming experience of men (21) and women ( 16) was statistically significant (p < 0.001). Experience maybe associated with a better understanding of climate change impacts and potential adaptation strategies (Batungwanayo et al, 2023), thereby explaining possible gender differences in choice or use of climate change adaptation strategies. The results also showed that almost all farmers (98%) in the study area relied on crop production as their main income source.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…This assertion is further supported statistically significantly high average farm size is owned/accessed by men farmers (4.5 acres) compared to women (4.4 acres). Thus, farmers with larger farms may have more resources and flexibility to implement certain strategies (Batungwanayo et al, 2023), thereby accounting for potential gender differences in climate change adaptation strategies.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The associated trends and events continue to lower agricultural land productivity, causing malnutrition, loss of livelihoods and hampering prosperity [4]. The effects are most pronounced and experienced in developing countries where rain-fed agriculture constitutes a major source of livelihood [5]. These impacts are also considered to be key drivers of human displacement and mass migrations [6], increased vulnerability of women and girls to violence (Nerini et al, 2019) and increased gender inequalities, such as the withdrawal of girls from school [7].…”
Section: Introductionmentioning
confidence: 99%
“…The associated trends and events continue to lower agricultural land productivity, causing malnutrition, loss of livelihoods and hampering prosperity (Ruwoldt, 2013;Singh et al, 2014). The effects are most pronounced and experienced in developing countries where rain-fed agriculture constitutes a major source of livelihood (Nkuba et al 2020a;Omotoso et al 2023;Batungwanayo et al 2023). These impacts are also considered to be key drivers of human displacement and mass migrations (Orhan 2018), increased vulnerability of women and girls to violence (Nerini et al, 2019) and increased gender inequalities such as the withdrawal of girls from school (Ampaire et al 2020).…”
Section: Introductionmentioning
confidence: 99%